2014
DOI: 10.2527/jas.2013-7374
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of molecular breeding values for Warner-Bratzler shear force and carcass traits of beef cattle – An independent validation study1

Abstract: Interest in genetic improvement of carcass and tenderness traits of beef cattle using genome-based selection (GS) and marker-assisted management programs is increasing. The success of such a program depends on the presence of linkage disequilibrium between the observed markers and the underlying QTL as well as on the relationship between the discovery, validation, and target populations. For molecular breeding values (MBV) predicted for a target population using SNP markers, reliabilities of these MBV can be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…The numbers of observations, phenotypic means, and standard deviations for the studied traits are summarized in Table 2. Consistent with previous studies, there was substantial phenotypic variation in this sample of crossbred beef cattle (Akanno et al 2014a(Akanno et al , 2014b. The proportions of total phenotypic variance explained by all genetic effects according to the model defined for Fig.…”
Section: Prediction Of Genomic Breed Compositionsupporting
confidence: 75%
“…The numbers of observations, phenotypic means, and standard deviations for the studied traits are summarized in Table 2. Consistent with previous studies, there was substantial phenotypic variation in this sample of crossbred beef cattle (Akanno et al 2014a(Akanno et al , 2014b. The proportions of total phenotypic variance explained by all genetic effects according to the model defined for Fig.…”
Section: Prediction Of Genomic Breed Compositionsupporting
confidence: 75%
“…Bolormaa et al (2013b) found that this increased accuracy slightly (0.33 to 0.38) but not as much as if the same number of animals had been from the same breed. When Akanno et al (2014) used a reference population of several pure breeds in USA to predict within a crossbred population in Canada, the accuracy was low. If the target breed is not included in the reference population, the accuracy is very low.…”
Section: Genomic Selection In Beef Cattlementioning
confidence: 99%
“…For slaughter, animals were first stunned by captive bolt and then exsanguinated. Collection of carcass data was previously described [53,55,[59][60][61][62]. Briefly, hot carcass weight (HCW) in kg was obtained by summing up the weight of each side of the carcass that was split during dressing, about 45 min post-mortem.…”
Section: Animal Populations and Phenotype Datamentioning
confidence: 99%